Stage‑specific Plasmodium falciparum immune responses in afebrile adults and children living in the Greater Accra Region of Ghana - Acquah, F.K.; Lo, A.C.; Akyea‑Mensah, K.; Abagna, H.B.; Faye, B.; Theisen, M.; Gyan, B.A.; Amoah, L.E. (Malaria Journal, 2020)
Background: Asymptomatic carriage of Plasmodium falciparum is widespread in adults and children living in malaria-endemic countries. This study identified the prevalence of malaria parasites and the corresponding levels of naturally acquired anti-parasite antibody levels in afebrile adults living in two communities in the Greater Accra Region of Ghana. Methods: Two cross-sectional studies conducted in January and February 2016 and repeated in July and August 2016 recruited subjects aged between 6 and 75 years from high parasite prevalence (Obom) and low parasite prevalence (Asutsuare) communities. Whole blood (5 ml) was collected from each volunteer, plasma was aliquoted and frozen until needed. An aliquot (10 μl) of the blood was used to prepare thick and thin blood smears, 100 μl was preserved in Trizol and the rest was separated into plasma and blood cells and each stored at − 20 °C until needed. Anti-MSP3 and Pfs230 antibody levels were measured using ELISA. Results: Asexual parasite and gametocyte prevalence were higher in Obom than Asutsuare. Antibody (IgG, IgG1, IgG3, IgM) responses against the asexual parasite antigen MSP3 and gametocyte antigen Pfs230 were higher in Obom during the course of the study except for IgM responses against Pfs230, which was higher in Asutsuare than in Obom during the rainy season. Antibody responses in Asutsuare were more significantly associated with age than the responses measured in Obom. Conclusion: The pattern of antibody responses measured in people living in the high and low malaria transmission setting was similar. All antibody responses measured against the asexual antigen MSP3 increased, however, IgG and IgG1 responses against gametocyte antigen Pfs230 decreased in moving from the dry to the peak season in both sites. Whilst asexual and gametocyte prevalence was similar between the seasons in the low transmission setting, in the high transmission setting asexual parasite prevalence increased but gametocyte prevalence decreased in the rainy season relative to the dry season.
Research Article
Keywords: Transmission; Gametocyte; Afebrile; Antibody